GmBTB/POZ, a novel BTB/POZ domain‐containing nuclear protein, positively regulates the response of soybean to Phytophthora sojae infection. (16th October 2018) - Zhang, Chuanzhong; Gao, Hong; Li, Rongpeng; Han, Dan; Wang, Le; Wu, Junjiang; Xu, Pengfei; Zhang, Shuzhen
Summary: Phytophthora sojae is a destructive pathogen of soybean [ Glycine max (L.) Merr.] which causes stem and root rot on soybean plants worldwide. However, the pathogenesis and molecular mechanism of plant defence responses against P. sojae are largely unclear. Herein, we document the underlying mechanisms and function of a novel BTB/POZ protein, GmBTB/POZ, which contains a BTB/POZ domain found in certain animal transcriptional regulators, in host soybean plants in response to P. sojae . It is located in the cell nucleus and is transcriptionally up‐regulated by P. sojae . Overexpression of GmBTB/POZ in soybean resulted in enhanced resistance to P. sojae . The activities and expression levels of enzymatic superoxide dismutase (SOD) and peroxidase (POD) antioxidants were significantly higher in GmBTB/POZ ‐overexpressing ( GmBTB/POZ ‐OE) transgenic soybean plants than in wild‐type (WT) plants treated with sterile water or infected with P. sojae . The transcript levels of defence‐associated genes were also higher in overexpressing plants than in WT on infection. Moreover, salicylic acid (SA) levels and the transcript levels of SA biosynthesis‐related genes were markedly higher in GmBTB/POZ ‐OE transgenic soybean than in WT, but there were almost no differences in jasmonic acid (JA) levels or JA biosynthesis‐related gene expression between GmBTB/POZ ‐OE and WT soybean lines. Furthermore, exogenous SA application induced the expression of GmBTB/POZ and inhibited the increase in P. sojae biomass in both WT and GmBTB/POZ ‐OE transgenic soybean plants. Taken together, these results suggest that GmBTB/POZ plays a positive role in P. sojae resistance and the defence response in soybean via a process that might be dependent on SA.